The effect of the extract from chickens embryos on the state of intestinal microflora of mice at total single γ-irradiation - Погоріла, М. С.; Жегунов, Г. Ф.; Щербак, О. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2013)
In the experiment in vivo using females of white laboratory mice, that were subjected to single total gamma irradiation, there has been investigated the action of a series of intramuscular introductions of the extract from chickens embryos on the state of intestinal microflora. Intramuscular administration of the extract from chickens embryos promotes restoration of the normal state of intestinal microflora of mice in the experiment.